Percorrendo o caminho do Tenchi Tessen a partir da teoria psicanalítica: o self, o movimento e a criatividade. - Cavalcanti, Amanda Pereira (2020)
This research paper had in its goal to reflect on TenChi Tessen from Winnicott’s psychoanalytic theory, aiming to estabilish the possible relations between the practice of TenChi Tessen’s movements and the expression of true self. The choice of this art form as the main subject of study was made because of our familiarity with it, which is imperative for the emergence of questionings fundamental to paving this path. Considering TenChi Tessen is defined as a Do (Way), its movements offer the practitioner the possibility of an encounter with themselves. For us to wander the proposed path, theorical research became a crucial element and gave rise to the following main goal: to reflect on TenChi Tessen from Winnicott’s psychoanalytic theory, aiming to establilish the possible relations between the practice of TenChi Tessen movments and the expression of true self. The specific goals are as follows: a) To comprehend the development of the self concept to the psychoanalytic theory; b) To estabilish the possible relations between movement and the expression of true self according to Winnicott’s chain of thought; c) To describe the art of TenChi Tessen and its main movements and d) To analyze the possible relations between the practice of TenChi Tessen and the expresson of true self. The hermeneutic conception of Reading was preferred due to its proposal, which makes it possible for the reader to interpret the work according from their personal experiences. Such modality made the articulation bewteen the key themes of each chapter possible and fed the building of the final analysis, which was composed of analogies built from the correlation between the main fundamentals of art and Winnicott’s chain of thought. During this path, the dimension of the self was featured so to draw nearer to the notion of movement, which, by revealing the innate potencial of the human being, is capable of revealing its singularity, through “spontaneous gestures” and creative actions, permitting the thought of the movement of the body as the one to open na aura of possibilities of creativity expression, which indicates the rising of the self. With this research paper, we hope to contribute to reflecting on the role of the movement as a fundamental aspect of one’s health or sickening proccess, as well as establishing the the movement arts as facilitators of the search whithin one’s interior dimension and expression of true self.